Intra‐hospital dissemination of clinical and environmental isolates of Stenotrophomonas maltophilia from Tehran. (1st March 2021) - Kardan‐Yamchi, J.; Hajihasani, A.; Talebi, M.; Khodaparast, S.; Azimi, A.; Rahbar, M.; Fallah, F.; Douraghi, M.
Abstract: Stenotrophomonas maltophilia isolates are responsible for various hospital‐acquired infections and are particularly increasing in the immunocompromised patients. The aim of this study was to determine the clonal relatedness between S. maltophilia isolates originating from the clinic and environment. A total of 150 S. maltophilia isolates from patients and 1108 environmental samples obtained in three hospitals from Tehran. Following molecular identification targeting 23S rRNA gene, the clonal relatedness of the environmental and clinical isolates was determined using pulsed field gel electrophoresis (PFGE). Of the 150 clinical and 18 environmental isolates identified using phenotypic tests, the speciation of 120 and 15 was confirmed by targeting the 23S rRNA gene. The 24 common pulsotypes (PTs) and 32 single PTs were identified by PFGE. Only a small cluster was shared among the clinic and environment within a hospital; therefore, the intra‐hospital dissemination of certain isolates of S. maltophilia among the clinic and environment was demonstrated.